Obtenção e caracterização de novas dispersões sólidas do antimicrobiano claritromicina - LUZ, Danilo Silva (2022)
Clarithromycin (CLA) is an antibiotic used to treat diseases caused by bacteria, such as leprosy. CLA belongs to class II of the biopharmaceutical classification system (SCB), as it has low water solubility and high membrane permeability, contributing to the reduction of its bioavailability and therapeutic efficacy. Obtaining solid drug dispersions (DSFs) is a viable alternative to improve physicochemical properties, such as aqueous solubility. This study aimed to obtain and characterize new CLA DSFs using oxalic acid (OXA) as a coformer, via slow evaporation of the solvent. Initially, molecular modeling of CLA and OXA was carried out to understand the interactions at the molecular level between the compounds, these presented low values of softness (S), with the potential to interact in the neutral state. CLA-OXA DSFs were obtained via slow solvent evaporation (SLS). For that, the starting compounds were weighed and their masses were solubilized in 20.00 mL methanol. The resulting solutions were allowed to stand at room temperature (25 ± 1 oC) until the complete evaporation of the solvent. For comparison purposes, the starting compounds were characterized before and after being submitted to ELS. Then, the starting compounds (non-recrystallized and recrystallized), salts and co-amorphous were characterized by powder X-ray diffraction (XRPD), Fourier transform infrared spectroscopy (FT-IR), spectroscopy by UV-vis diffuse reflectance (ERD), simultaneous thermogravimetry, derivative thermogravimetry and differential thermal analysis (TG/DTG-DTA) and differential scanning calorimetry (DSC). The results obtained by XRPD showed the formation of two new crystalline materials for the CLA-OXA binary mixture in molar ratios of 3:1 and 2:1 and of two new materials of amorphous nature for CLA-OXA (1:2) and (1:3). The FT-IR spectra obtained for these new materials showed changes in relation to the spectra presented for the starting compounds, evidencing the occurrence of intermolecular interaction between the hydroxyl groups of CLA and the carboxyl groups of OXA. In the UV-VIS analysis of the salts, a reduction of the OXA bands was observed, the co-amorphs did not show reflectance. The endothermic curves obtained by simultaneous TG/DTG-DTA of the salts, it was possible to observe the absence of the OXA sublimation event and the salt melting event, the co-amorphs presented the anticipation of the material sublimation event. The thermal curves obtained by the DSC analysis of the salts showed the melting of the material at a temperature earlier than the melting event of CLA, the co-amorphous registered sublimation events at lower temperatures when compared to the sublimation of OXA. In this way, the results acquired in this study confirmed the obtaining of four new solid dispersions of CLA-OXA, two of the salt type and two co-amorphous. These new materials showed promise for increasing the water solubility and CLA dissolution rate.